Extra- and Intraoral Clinical Findings of Recessive Dystrophic Epidermolysis Bullosa: A Case Report - NAMDAR PEKİNER, FİLİZ MEDİHA; KURU, LEYLA; AĞRALI, ÖMER BİRKAN (AVES PRESS LTD, 2016)
Epidermolysis bullosa (EB) is a heterogeneous group of inherited blistering mucocutaneous disorders that have a specific defect in the attachment mechanisms of the epithelial cells, either to each other or to the underlying connective tissue. Recessive dystrophic type EB (Hallopeau-Siemens syndrome) represents repeated episodes of cutaneous breakdown, which heal with scarring, resulting in the fusion of the fingers into a mitten-like deformity. The vesicle/bulla can be intraorally observed and the depth of the buccal vestibule may decrease because of scarring. In this case report, the intra-/extraoral findings of a 25-year-old male patient, who was diagnosed with recessive dystrophic type EB immediately after birth, are presented. Extraoral examination revealed mitten-like hands and feet because of scar tissue formations on the hands and feet. Similarly, during intraoral examination, scar tissue formations were observed that had caused denuded mouth opening and limited tongue functions. In addition, periodontal problems and dental caries were observed because of limited plaque control. This case report emphasizes the importance of knowledge regarding patients with EB and presents some intraoral findings.
Keywords: Oral manifestations; Hallopeau-Siemens disease; epidermolysis bullosa dystrophica; case report